TEACHER’S PERSPECTIVE : ENGLISH IN ELEMENTARY SCHOOL, IS IT NECESSARY OR NOT? - titin kustini (Universitas Majalengka, 2021)
The Covid 19 pandemic which requires online learning has caused learning difficulties for students at the junior high school level, especially in English subjects which they have only formally get because in elementary school there are no more English lessons. Especially in rural areas where students' insight is very limited and parents’ ability to assist their children in learning is also quite limited, it is become a big problem. English is really a new thing that they get, while with face-to-face learning, they lost opportunities to ask and discuss learning difficulties to their teacher. This study aims to find out how the perspective of elementary school teachers on English lessons, whether they consider it necessary or not if English is taught since elementary school related to a lot of students find difficulties to learn English in junior high school. 9 teachers participated in this research. They are spread evenly in various places in Majalengka district. Data were obtained through observation, questionnaires and interviews by google form and whatsapp and analyzed by qualitative. The results of the study finds that 100% of the teachers agreed English should taught in elementary schools. The obstacles might be faced if English is applied in elementary schools, 55,5 % said facilities and infrastructure, 22,2% said nothing and 11,1% students’ interest in learning english and 11,1% said that they don’t have English teacher. And their expectations are students able to speak in daily conversation (22,2%) and 77,8% hope students know basic english to make them easier in learning English at the next level.